Epizootological investigation on Leishmaniosis (L. Donovani) on dogs of the district of Cephallonia - ΑΡΤΑΒΑΝΗΣ, ΣΠ.; ΤΣΟΥΤΣΑΝΗΣ, Κ.; ΒΡΑΚΑΣ, Α.; ΤΣΙΛΙΟΣ, Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
An epizootoligical investigation on leishmaniosis (L. Donovani) was carried out on dogs in the district of Cephailonia island, particularly on areas where human cases were identified. The investigation was based on: a) Dogs's blood samples examination by the formaldehyde test, b) Sternum and lymphodes material examination taken by puncture, c) Phlebotomus and rats examination captured in the areas where the investigation was performed. From the 1800 samples examined, 70 were positive to the formaldehyde test. Among these 70 dogs, 58 were manifestating clinical symptoms. Sternum smear examination from the remaining 12 were positive to Leishmania in 3 cases. Among 15 dogs negative to the formaldehyde test, although with characteristic clinical symptoms, Leishmaniae were identified in 12 sternum smears. 2 out of the remaining 3 cases were positive to the fluorescence technique examination.